Using modern mechanical design methods for determining the main characteristics of a cryogenic centrifugal pump - Rogovyi, Andrii; Shudryk, Oleksandr; Tulska, Alona Gennadiivna; Basova, Yevheniia; Rezvaya, Kseniya Sergeevna; Makarov, Vadym; Lazaryeva, Olha; Antosz, Katarzyna; Machado, José (National Institute of Research and Development in Mechatronics and Measurement Technique, 2023)
The paper is devoted to the study of the flow structure of liquid nitrogen in centrifugal pumps and determination of the energy and kinematic characteristics of the flow in the impeller of the support cryogenic pump of the mobile nitrogen units. An analysis of modern technical solutions in this field was made identifying their advantages and disadvantages. The work examines the processes and specifics of the flow of liquid nitrogen in the impeller flow part. Integral characteristics, such as differential pressure (head) and hydraulic efficiency, of the impeller during pumping liquid nitrogen and water were obtained using modern modelling tools. An increase in hydraulic losses in the impeller during pumping of liquid nitrogen in the area containing curved channels and rotation was detected. This contradicts the tendency of loss reduction in a fixed pipe, where differential pressure is much smaller than during pumping water. A study of different configurations of booster pumps was made. According to mechanical approaches to the hydraulic equipment design, it was justified that reduced number of impeller blades (4 blades) ensures the operation of the unit in a required efficiency range. As a result of spatial modelling of the flow using the free open source CFD software OpenFOAM, distributions of the main kinematic characteristics of the flow were obtained. It was found that the physical properties of liquid nitrogen do not have a significant effect on the main parameters of centrifugal pumps, such as efficiency and pressure (thehydraulic efficiency during pumping of liquid nitrogen is only 2-5% lower than during pumping water).
Keywords: mechanical design; booster pump; liquid nitrogen; impeller; turbulence; differential pressure; velocity profile; viscosity